PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMPENSASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DAN KINERJA PEGAWAI DINAS PENDAPATAN DAERAH KOTA PONTIANAK - PRATAMA ILHAM SAFITRIE B2042131035 (Universitas Tanjungpura, 2017)
This research aims to analyze the effects of transformational of leadership style and Compensation on Organizational Citizenship Behavior and the effects of transformational leadership style, compensation, and Organizational Citizenship Behavior on employees’ performance at the Revenue and Tax Office of Pontianak City. In this research, data colletion was carried out through a questionnaire distributed to employees of the Revenue and Tax Office of Pontianak. The research method is a survey research using the instrument of questionnaire to obtain primary data from respondent. The data analysis technique used the path analysis. The results of this research indicate that transformational leadership style variable had a significant effect on Organitazional Citizenship Behavior, but had no effect on performance; meanwhile Organitazional Citizenship Behavior had an effect on performance. Keywords: Transformational leadership style, Compensation, Organizational, Citizenship Behavior, and Performance.